Psoriasis: Unraveling Disease Mechanisms and Advancing Pharmacological and Nanotechnological Treatments - Miao M; Yan J; Sun Y; Liu J; Guo S (Journal of Inflammation Research)
Miao Miao,1 Jiong Yan,2 Yujin Sun,3 Jia Liu,2 Shun Guo2 1Outpatient Department, Disease Prevention and Control Center of Tongshan District, Xuzhou, People’s Republic of China; 2Dermatology, Affiliated Hospital of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 3Dermatology, Affiliated Hospital of Xuzhou Medical University, Xuzhou, People’s Republic of ChinaCorrespondence: Jia Liu; Shun Guo, Affiliated Hospital of Nanjing University of Chinese Medicine, 155 Hanzhong Road, Qinhuai District, Nanjing, Jiangsu Province, 210029, People’s Republic of China, Email aliceyoyo1986@163.com; 260873@njucm.edu.cnAbstract: Research into the pathogenesis of inflammatory skin diseases, including dermatitis and psoriasis, has yielded significant advancements in the last decades. The identification of age, gender, and genetic factors contributing to these complex conditions has been pivotal in developing novel pharmacological and technological treatments. This review delves into the molecular underpinnings of psoriasis, examining current therapies and promising investigational agents. We highlight the potential of nanotechnology to enhance drug delivery to affected skin areas, with microneedles emerging as a promising platform for psoriasis and other chronic inflammatory skin diseases.Keywords: biodegradable nanoparticles, clinical trials, skin inflammatory diseases, psoriasis, microneedles